Breast Cancer and Breast Reconstruction - Tejedor, Luis; Gómez Modet, Susana; Manchev, Lachezar; Aditya Parikesit, Arli (IntechOpen, 2020)
This book has been contrived to gather recent data on a common health problem. As breast cancer imposes a heavy burden for society due to its psychological, social and economic consequences, every step to broaden our understanding is a worthy task. The aim of this book is to provide some insights on this subject through the information given on new perspectives in genetics and diagnosis, exposed in the section on oncologic issues, as well as on recent topics on surgical treatment, presented in the sections on breast conservative and breast reconstructive surgery.